2014
DOI: 10.1097/aln.0000000000000307
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Drugs for Prevention of Acute and Chronic Postsurgical Pain

Abstract: There is currently insufficient evidence to support the clinical use of antidepressants-beyond controlled investigations-for treatment of acute, or prevention of chronic, postoperative pain. Multiple positive trials suggest the therapeutic potential of antidepressants, which need to be replicated. Other nontrial evidence suggests potential safety concerns of perioperative antidepressant use. Future studies are needed to better define the risk-benefit ratio of antidepressants in postoperative pain management. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 62 publications
(113 reference statements)
0
20
0
3
Order By: Relevance
“…42 However, a recent review article evaluating the use of tricyclic antidepressants (TCAs) for the prevention of acute or chronic pain revealed therapeutic potential for TCAs, but evidence was lacking to support the clinical use of TCAs beyond controlled investigations. 43 One study exists demonstrating the effective use of amitriptyline for the treatment of neuropathic pain in dogs. 44 Therefore, the evidence supporting the use of TCAs in the management of acute pain in the dog is currently insufficient.…”
Section: Tricyclic Antidepressantsmentioning
confidence: 99%
“…42 However, a recent review article evaluating the use of tricyclic antidepressants (TCAs) for the prevention of acute or chronic pain revealed therapeutic potential for TCAs, but evidence was lacking to support the clinical use of TCAs beyond controlled investigations. 43 One study exists demonstrating the effective use of amitriptyline for the treatment of neuropathic pain in dogs. 44 Therefore, the evidence supporting the use of TCAs in the management of acute pain in the dog is currently insufficient.…”
Section: Tricyclic Antidepressantsmentioning
confidence: 99%
“…A systemic review of antidepressants by Wong et al [22] showed potential therapeutic benefits of antidepressants in certain postoperative clinical settings. Some controlled investigations showed benefit of antidepressants for treatment of acute or prevention of chronic postoperative pain.…”
Section: Antidepressantsmentioning
confidence: 99%
“…As classes mais comuns de antidepressivos incluem os seguintes: antidepressivos tricíclicos, inibidores seletivos da recaptação de serotonina e noradrenalina. 36 Além da inibição seletiva da recaptação de serotonina e noradrenalina, os antidepressivos podem antagonizar os canais de sódio periféricos e receptores N-metil-D-aspartato (NMDA). Estes mecanismos diminuem a sensibilização central que são importantes na fisiopatologia da dor aguda pós-operatória.…”
Section: Antidepressivos E Dor Pós-operatóriaunclassified
“…Estes mecanismos diminuem a sensibilização central que são importantes na fisiopatologia da dor aguda pós-operatória. 36 Um conceito presente, ainda atualmente, em relação ao uso de antidepressivos está relacionado ao tempo de início de ação, considerado em torno de 7 a 10 dias, o que seria ilógico seu uso em dores agudas. Porém, estudos recentes sobre antidepressivos para controle de dor pós-operatória têm suscitado o entusiasmo para esta potencial nova indicação.…”
Section: Antidepressivos E Dor Pós-operatóriaunclassified
See 1 more Smart Citation